The Influence of Qur’anic Stories on Students - Rosdiani Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Qur’anic story is one of the educational methods that holds an important position within the Islamic education system. The Qur’an, as the primary source of Islamic teachings, contains many stories that are not merely historical narratives but are rich with educational, moral, spiritual, and psychological values. This article aims to describe the influence of Qur’anic stories on students, particularly in the aspects of emotion, motivation, value internalization, and the formation of thought patterns. This study employs a qualitative approach through a literature review of classical and contemporary sources regarding the storytelling method in Islamic education. The findings indicate that Qur’anic stories have a strong impact on the development of students’ personalities because they can touch affective aspects, build internal motivation, and foster moral and spiritual awareness. Therefore, the Qur’anic storytelling method is relevant for implementation in contemporary Islamic education as a strategy for character formation.